Sleep patterns and match performance in elite Australian basketball athletes. Issue 8 (August 2017) - Staunton, Craig; Gordon, Brett; Custovic, Edhem; Stanger, Jonathan; Kingsley, Michael
Abstract: Objectives: To assess sleep patterns and associations between sleep and match performance in elite Australian female basketball players. Design: Prospective cohort study. Methods: Seventeen elite female basketball players were monitored across two consecutive in-season competitions (30 weeks). Total sleep time and sleep efficiency were determined using triaxial accelerometers for Baseline, Pre-match, Match-day and Post-match timings. Match performance was determined using the basketball efficiency statistic (EFF). The effects of match schedule (Regular versus Double-Header; Home versus Away) and sleep on EFF were assessed. Results: The Double-Header condition changed the pattern of sleep when compared with the Regular condition (F(3, 48) = 3.763, P = 0.017), where total sleep time Post-match was 11% less for Double-Header (mean ± SD; 7.2 ± 1.4 h) compared with Regular (8.0 ± 1.3 h; P = 0.007). Total sleep time for Double-Header was greater Pre-match (8.2 ± 1.7 h) compared with Baseline (7.1 ± 1.6 h; P = 0.022) and Match-day (7.3 ± 1.5 h; P = 0.007). Small correlations existed between sleep metrics at Pre-match and EFF for pooled data (r = −0.39 to −0.22; P ≥ 0.238). Relationships between total sleep time and EFF ranged from moderate negative to large positive correlations for individual players (r = −0.37 to 0.62) and reached significance for one player (r = 0.60; P = 0.025). Conclusions: Match schedule can affect the sleep patterns of elite female basketball players. A large degree of inter-individual variability existed in the relationship between sleep and match performance; nevertheless, sleep monitoring might assist in the optimisation of performance for some athletes.